A review on gold nanoparticles (GNPs) and their application in cancer therapy - Hamza , Zaman S.; Al-Ajeeli , Zahraa A. Al-; Hussein, Mustafa jaafar (Jour Med Resh and Health Sci, 2023)
Global Cancer Treatment (GLOBOCAN) claims that almost 18 million new cases of cancer are recorded each year. Chemotherapy, radiation, and surgery have historically been the most popular types of cancer treatment. The maximum tolerable dose is now the guideline for treating patients. It will be critical to address normal tissue toxicity, which is one of the major problems with both chemotherapy and radiation therapy. The development of contemporary nanoparticle-based approaches could help with this. Due to the fact that they release chemotherapeutics under controlled conditions, devices based on gold nanoparticles (GNP) are particularly beneficial in further strengthening chemotherapy. Nonetheless, by aiming the GNPs at the tumor, the local radiation dosage may be increased. More than 20 therapeutic drugs based on nanotechnology have entered the clinical stage in the past 20 years. Using a GNP-based therapeutic system more swiftly in clinical settings while lowering normal tissue toxicity and increasing treatment effectiveness is the main objective of this review paper. Nanomedicines will enhance and lessen the side effects of future cancer therapies.